2012
DOI: 10.1007/s11033-012-1885-4
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation in primary squamous cell carcinoma of the oral cavity and oropharynx: a study of a Brazilian cohort

Abstract: Epigenetic silencing of cancer-related genes plays an important role in oral/oropharyngeal squamous cell carcinoma (OSCC). We evaluated promoter hypermethylation of 4 cancer-related genes in OSCCs of a Brazilian cohort and determined its relationship with exposure to alcohol, tobacco, HPV infection and clinicopathological parameters. CDKN2A (cyclin-dependent kinase inhibitor 2A or p16), SFN (stratifin or 14-3-3 σ), EDNRB (endothelin receptor B) and RUNX3 (runt-related transcript factor-3) had their methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen articles met the inclusion criteria and were eligible for further analysis. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The main reasons for exclusion were duplicates and studies not investigating correlation between HPV status and methylation status in OPSCC.…”
Section: Search Resultsmentioning
confidence: 99%
“…28,33,34,44 In other publications studying overall HNSCC, OPSCC subgroup size ranged from 9% to 80% of the total study population. [29][30][31][32][35][36][37][38][39][40][41][42][43] There was only one study that reported the distribution of average age, nicotine and alcohol consumption between HPV-positive and HPV-negative tumors of which promoter methylation was evaluated. 34 The mean age in HPV-positive tumors was 56.9 compared with 58.4 in HPV-negative tumors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations